Tajikistan Country Economic Update, Fall 2017 : Heightened Vulnerabilities Despite Sustained Growth - World Bank Group (World Bank, Washington, DC, 2017)
This edition of the Tajikistan Country Economic Update (CEU) is part of a semi-annual series designed to monitor socio-economic developments in Tajikistan. In the first half of 2017, total investment was down by over seventeen percent year on year. However, investment picked up markedly in the third quarter, resulting in a year-on-year increase of twenty two percent compared to the first nine months of 2016. This report presents an analysis of political, economic and social developments, as well as the progress of and challenges with the implementation of structural reforms in 2017. It also includes a special section highlighting the key fiscal management challenges in Tajikistan.